IMPLEMENTASI ETIKA BISNIS ISLAM DALAM MENGHADAPI PERSAINGAN BISNIS PADA PT. BRECXELLE BERKAH UNITI - Hanifah, Risma; Zulkarnain, Lutfi (GREAT: Jurnal Manajemen dan Bisnis Islam, 2024)
The purpose of this study is to answer how to analyze the principles of Islamic business ethics implemented by PT. Brecxelle Berkah Uniti is facing business competition. The writing method used is descriptive qualitative with field research. For data collection, the authors conducted observations and interviews with informants in this study, namely the main director of PT. Brecxelle Berkah Uniti. The results of this study concluded that PT. Brecxelle Berkah Uniti has implemented five principles of Islamic business ethics. The principle of unity (tawhid), PT. Brecxelle Berkah Uniti believes that Allah has arranged sustenance. The principle of balance (fairness), PT. Brecxelle Berkah Uniti uses measuring instruments as measurements in forming its products. The principle of free will, PT. Brecxelle Berkah Uniti can fulfill the mutually agreed upon agreement. The principle of responsibility, PT. Brecxelle Berkah Uniti can fulfill employee salaries by the initial agreement. The principle of virtue (ihsan), PT. Brecxelle Berkah Uniti can create jobs for the surrounding environment.